PENGARUH KARAKTERISTIK INDIVIDU, KOMITMEN ORGANISASI DAN MOTIVASI FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT UNIRAMA KAPAL - I Putu Gian Kumara Putra; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
The potential of human resources is essentially one of the capital and plays the most important role in achieving company goals. Increasing employee performance will bring progress for the company to be able to survive in an unstable competitive business environment. Therefore, efforts to improve employee performance are the most serious management challenges due to success in achieving company goals and survival of the company depends on the quality of the performance of the human resources in it. The purpose of the study was to determine and analyze whether individual characteristics, organizational commitment and financial motivation affect the performance of employees at the company PT. Unirama Kapal The sample in this study were all active employees of PT Unirama Kapal as many as 71 people. The sampling technique used is the saturated sampling method. Data collection techniques used in this study were observation, interviews and questionnaires. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation analysis, analysis of determination (R2), f test and t test. The results show that individual characteristics, organizational commitment and financial motivation have a positive and significant impact on employee performance, so it is better for leaders to provide better job skills training in order to increase the ability of each individual employee, provide a comfortable work environment and provide benefits or bonuses. to outstanding employees to spur the improvement of other employees' work, so as to improve employee performance at PT. Unirama Kapal